ACTIVITIES OF DISABLED CRAFTSMANSHIP ARTELLARI IN SURKHANDARYA REGION IN THE 1950S AND 1980S AND TYPES OF PRODUCTS PRODUCED BY THEM (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
This article describes the creation of cooperatives of disabled people in the southern regions of Uzbekistan, namely the Surkhandarya region, in the 1950s-1980s, as well as the activities of the artisan artels attached to them and the types of products they produce. On the basis of periodicals and archival materials, the creation of the first enterprise for the disabled in the region in the Denovsky district and the activities of the Termez enterprise for the blind are highlighted.